Petroleum Funds as Instruments of Energy Policy and Economic Diversification: A Cross-Country Integrative Review - Mota, Teodoro Marcos; Adityawarman, Adityawarman; Ariadji, Tutuka; Naikosou, Marcelino Freitas; Guterres, Mario Viana; Samawi, Nabil Visi; Hidayat, Miftah; Siagian, Utjok W. R.; Dewi, Retno Gumilang; Saldanha, Estanislau de Sousa (International Journal of Energy Economics and Policy, 2025)
This study offers an integrative literature analysis on petroleum funds in 17 resource-rich nations, including governance frameworks, investment strategies, disbursement processes, and project financing decisions. Petroleum funds are crucial tools for sustaining oil-dependent economies, maintaining intergenerational justice, and promoting economic diversification. The research identifies considerable variations in fund efficacy, which are caused by variances in legislative structures, fiscal norms, transparency, and alignment with national development goals. Best practices can be seen in nations such as Norway and Timor-Leste, where rule-based governance and sustainability frameworks are promoted. In contrast, Nigeria, Libya, and Angola confront issues due to political meddling and lax institutional governance. The report also looks at developing trends including the incorporation of Environmental, Social, and Governance (ESG) criteria and the strategic role of sovereign wealth funds in managing energy transitions. The findings show that, while no uniform model exists, open governance, sustainable fiscal policies, and strategic investment alignment improve petroleum fund performance. This study provides policymakers with significant insights on how to maximize petroleum fund management in the face of global economic volatility and altering energy landscapes.